Physician self-reported factors driving clinical decision-making in management of patients with T2D and ASCVD/high risk of ASCVD across the middle East and Africa: a cross-sectional study - Salek, Sam; Sabbour, Hani; Alamuddin, Naji; Alawadi, Fatheya; Alkandari, Hessa; Almahmeed, Wael; Assaad-Khalil, Samir H.; Ceyhan, Emel Mashaki; Haddad, Jihad; Lombard, Landman; Ngome, Mary; Malik, Rayaz A.; et al. (Frontiers in Pharmacology, 2025)
AimsTo explore factors influencing the clinical decision-making of physicians treating patients with type 2 diabetes (T2D) and high risk of atherosclerotic cardiovascular disease (ASCVD) across seven Middle Eastern and African countries.MethodsCross-sectional, anonymous online study of self-reported factors driving clinical decision-making for the management of T2D based on agreement with statements using a five-point Likert scale among physicians (n = 385) in Bahrain, Egypt, Jordan, Kuwait, Qatar, South Africa, and UAE between June 13 and October 1, 2022.ResultsFrom a selection of patient factors, physicians were most likely to agree that treatment adherence/compliance (92%), safety concerns (92%), and impact on health-related quality of life (88%) influenced their decision-making. Most physicians agreed that availability of treatment (87%) was a practice setting factor that influenced their decision-making. The top three physician factors influencing clinical decision-making included continuous medical education (96%), medical knowledge (96%), and international clinical guidelines (95%). Most physicians agreed that improved communication skills of physicians (97%), coaching and question prompts for patients (91%), and patient decision aids (87%) could improve shared decision-making.ConclusionVarious patient, practice, and physician factors influenced physicians’ management of their patients with T2D. Physicians believed improving their communication skills could improve shared decision-making.Clinical Trial RegistrationThe trial is registered with clinicaltrails.gov, Identifier #NCT05317845 (2023-03-28).